2014
DOI: 10.1097/mat.0000000000000127
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Glycemic Control After Left Ventricular Assist Device Implantation in Advanced Heart Failure Patients With Diabetes Mellitus

Abstract: Left ventricular assist devices (LVADs) have been shown to improve outcomes in advanced heart failure (HF). We hypothesized that LVADs improve glycemic control in HF patients with diabetes mellitus (DM). During a 6 year time period, 202 patients underwent mechanical circulatory support. Of these, 50 patients with DM were included. Data were collected within 2 months before LVAD implantation and at 5.6 ± 1.1 months post-LVAD implant. There was no significant difference in body mass index, hemoglobin, hematocrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…We assessed pre-LVAD hemoglobin A1c and found no significant difference in survival in diabetics with controlled diabetes (baseline HbA1c < 7%) compared with patients with poorly controlled diabetes (baseline HbA1c ≥ 7.0%). We and others have demonstrated improved glycemic control after LVAD implant in diabetic patients [1316]. The current study suggests that despite improved glycemic control, mortality remains high in diabetic LVAD patients.…”
Section: Commentmentioning
confidence: 48%
“…We assessed pre-LVAD hemoglobin A1c and found no significant difference in survival in diabetics with controlled diabetes (baseline HbA1c < 7%) compared with patients with poorly controlled diabetes (baseline HbA1c ≥ 7.0%). We and others have demonstrated improved glycemic control after LVAD implant in diabetic patients [1316]. The current study suggests that despite improved glycemic control, mortality remains high in diabetic LVAD patients.…”
Section: Commentmentioning
confidence: 48%
“…(Table 1). 6,[16][17][18][19][20][21][22][23][24][25][26][27] All studies were single-centre, retrospective observational investigations that utilized a pre-post design and were published as full-text articles, except one that is only available in abstract form. 16 Sample sizes ranged from 11 to 139 with durations of follow-up ranging from 126 days to 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Six studies 6,21,22,[25][26][27] reported changes in fasting blood glucose before and after LVAD implantation (Table S2). Pooled analysis showed a significant 24.4 mg/dL reduction at followup (95% CI À33.4 to À15.5) and little statistical heterogeneity (I 2 = 7%, Cochrane P = 0.37) ( Figure 3).…”
Section: Secondary Outcomesmentioning
confidence: 99%
See 2 more Smart Citations